2010
DOI: 10.1007/s12026-010-8170-1
|View full text |Cite
|
Sign up to set email alerts
|

Signaling through the P38 and ERK pathways: a common link between HIV replication and the immune response

Abstract: One of the defining characteristics of HIV is its ability to manipulate the human immune response to promote its own replication. Since the beginning of the epidemic, there has been controversy whether a robust immune response to the virus is beneficial or detrimental for the host. Therefore, the effects of HIV on signaling pathways and cytokine production need to be characterized in order to distinguish between protective immune responses and inappropriate immune activation. Cytokine and biomarker expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
59
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 80 publications
5
59
0
Order By: Relevance
“…We infer that the preferential binding of the HIV-1 envelope glycoprotein gp120 to 6-O-sulfated groups over 2-O-sulfated groups on syndecans (47) may further delay endocytosis (43), thereby favoring infectious entry via fusion with cellular rafts. Moreover, ligand binding to syndecan-1 activates ERK, and ERK activation has been shown to facilitate HIV-1 infectivity and the assembly and release of new virions (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…We infer that the preferential binding of the HIV-1 envelope glycoprotein gp120 to 6-O-sulfated groups over 2-O-sulfated groups on syndecans (47) may further delay endocytosis (43), thereby favoring infectious entry via fusion with cellular rafts. Moreover, ligand binding to syndecan-1 activates ERK, and ERK activation has been shown to facilitate HIV-1 infectivity and the assembly and release of new virions (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that inhibition of HIV expression by nuclear receptors correlates with NCoR binding the LTR (38) and that HDAC3 is critical for repressing HIV transcription (35,36). NCoR1 enhances HDAC3 activity, whereas GPS2 has been reported to inhibit Ras/MAPK signaling (24), which activates HIV transcription (62,63). Therefore, recruitment of this complex to the HIV LTR would repress HIV transcription by altering chromatin as well as compromising signals necessary for efficient transcription.…”
Section: Discussionmentioning
confidence: 99%
“…An important intracellular arm of the TCR response is regulated by the N-Ras GTPase that is activated at Golgi membranes downstream of Lck. [5][6][7][8][9] T-cell activation is thought to be beneficial to HIV-1 because it allows transcriptional activation of latent provirus and progression of the life cycle. However, activation-induced cell death after TCR engagement runs the risk of limiting the lifespan of productively infected cells and thus the amount of viral progeny produced.…”
mentioning
confidence: 99%